2015
DOI: 10.17219/acem/29183
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Vitamin D Level in Autoimmune Thyroiditis Patients and a Control Group in the Polish Population

Abstract: Background. Vitamin D, known for its role in calcium-phosphorus homeostasis, is also a significant immunomodulatory factor. Vitamin D deficiency has been reported in some autoimmune disorders. Recently, vitamin D level in autoimmune thyroiditis (HT -Hashimoto's thyroiditis) has become the subject of researchers' interest. Objectives. This study aims to assess vitamin 25-OH-D3 levels in HT patients in comparison to a control group in the Polish population. This would be the first attempt conducted in this regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 30 publications
0
9
1
2
Order By: Relevance
“…Among these, 9 studies were from Turkey [ 26 , 34 , 36 , 37 , 39 , 42 , 43 , 48 , 49 ], 3 each from Saudi Arabia [ 17 , 32 , 35 ], Poland [ 38 , 52 , 59 ], China [ 27 , 28 , 51 ] and Korea [ 54 , 55 , 58 ], 2 each from Egypt [ 50 , 60 ] and Italy [ 40 , 57 ] and one each from Belgium [ 25 ], Canada [ 33 ], Brazil [ 44 ], Japan [ 47 ], India [ 45 ], Sweden [ 46 ], Thailand [ 53 ], Greece, United States [ 56 ], and Ukraine [ 31 ]. Among the 35 studies, 29 recruited both genders [ 25 , 27 32 , 34 41 , 43 46 , 48 56 , 58 ], 4 only women [ 17 , 42 , 47 , 57 ], and 2 studies did not report the gender [ 26 , 33 ]. Eighteen studies mentioned BMI [ 27 , 28 , 30 , 31 , 33 , 35 , 36 , 40 , 45 , 47 , 50 53 , 55 58 ] and 26 studies pointed to the time of ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these, 9 studies were from Turkey [ 26 , 34 , 36 , 37 , 39 , 42 , 43 , 48 , 49 ], 3 each from Saudi Arabia [ 17 , 32 , 35 ], Poland [ 38 , 52 , 59 ], China [ 27 , 28 , 51 ] and Korea [ 54 , 55 , 58 ], 2 each from Egypt [ 50 , 60 ] and Italy [ 40 , 57 ] and one each from Belgium [ 25 ], Canada [ 33 ], Brazil [ 44 ], Japan [ 47 ], India [ 45 ], Sweden [ 46 ], Thailand [ 53 ], Greece, United States [ 56 ], and Ukraine [ 31 ]. Among the 35 studies, 29 recruited both genders [ 25 , 27 32 , 34 41 , 43 46 , 48 56 , 58 ], 4 only women [ 17 , 42 , 47 , 57 ], and 2 studies did not report the gender [ 26 , 33 ]. Eighteen studies mentioned BMI [ 27 , 28 , 30 , 31 , 33 , 35 , 36 , 40 , 45 , 47 , 50 53 , 55 58 ] and 26 studies pointed to the time of ...…”
Section: Resultsmentioning
confidence: 99%
“…Inconsistencies in terms of the season of sample collection could also influence our final results. Besides, it has been proven that the bioavailability of vitamin D diminishes among overweight/obese individuals [ 65 ]; however, most of the included articles disregarded BMI as a confounding factor and probable source of heterogeneity [ 17 , 18 , 25 , 26 , 29 , 32 , 34 , 37 39 , 41 44 , 46 , 48 , 49 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tamer et al identified lower 25(OH)D levels in individuals with HT versus control subjects, with a tendency for a higher prevalence of deficiency in patients with hypothyroidism than in those in euthyroidism [51]. Studies in other populations corroborated the association between lower levels of 25(OH)D and the risk of HT, namely Bozkurt et al 2013 [52]; Mansournia et al 2014 [53]; Vondra et al 2015 [7]; Maciejewski et al 2015 [54]; Kim D et al 2016 [55]; Giovinazzo et al 2017 [56]; Ke et al 2017 [57]; and Pergola et al 2018 [58].…”
Section: Data In Hashimoto's Thyroiditis/chronic Autoimmune Thyroiditismentioning
confidence: 96%
“…In recent years, scientists have also been interested in vitamin D deficiency in Hashimoto patients [27,28]. Numerous studies indicate a low content of this vitamin in the blood serum of patients with lymphocytic thyroiditis.…”
Section: Vitamin Dmentioning
confidence: 99%
“…Most of the available studies indicated an increase in vitamin D deficiency and its decreased concentration in the group of people with Hashimoto compared to the control group. The differences relate to the correlation of vitamin D concentration in relation to the hormonal activity of the thyroid gland and the activity of the autoimmune process in the assessment of antithyroid antibodies (Table 2) Table 2: A review of studies assessing the relationship between vitamin D levels and Hashimoto's disease [27,28,30,34,35,38].…”
Section: Vitamin Dmentioning
confidence: 99%